Effect of hot rolling temperature on microstructure evolution, deformation texture and nanoindentation properties of an intermetallic Ti-43Al-9V-0.2Y alloy. (February 2020) - Wang, Q.B.; Zhang, S.Z.; Zhang, C.J.; Song, Z.W.; Zhu, D.D.; Dong, D.; Zhang, S.L.
Abstract: In this paper, microstructure evolution, deformation texture and nanoindentation properties of an intermetallic Ti-43Al-9V-0.2Y (at. %) alloy have been investigated after hot rolled in α+β+γ (R#1) and β (R#2) phase field regions. The primary components of sample R#1 are (β+γ) mixture and (α2 +γ) lamellar structure. With the temperature increases to 1250 °C, the microstructure of R#2 shows a new characteristic of martensitic α2 and acicular γ phase. And γ phase has different precipitation mechanisms by hot rolling at 1200 °C and 1250 °C. In R#1, γ phase is obtained through three provenances, which are the precipitating from β to form (β+γ) mixture, the precipitating from α phase to form (α2 +γ) lamellar structure, and the remnant γ phase during cooling from α+β+γ phase field. However, for R#2, γ phase always nucleates and grows within β matrix. Meanwhile, microstructure evolution of R#2 is discussed. In addition, the increase in rolling temperature also results in a significant change of the fiber texture. Comparing with γ phase, β phase has the stronger texture, which is due to the formation of γ grain along the K-S orientation relationship in β phase. In R#1 state, β phase exhibits a typical {121} <1–11> texture, while γ phase shows {031} <−5-13> and {112} <1–10> texture. Aiming at R#2, β phase displays {010} <100> cube texture, and γ phase has {-215} <5–53> and Goss {110} <001> texture. The hardness ( H ) and reduced elastic modulus ( E r ) are investigated by nanoindentation. The (β+γ) mixture structure in R#2 has the highest H (12.63 GPa), whereas the E r is related to the microstructure composition. Highlights: Microstructure evolution and texture component are investigated by different rolling temperatures. The microstructure evolution of martensitic α2  and acicular γ is defined. The γ grain has different precipitation mechanisms with samples rolling at 1200 °C and 1250 °C. The hardness and reduced elastic modulus are investigated by nanoindentation.